The use of translanguaging to facilitate students’ English learning in an Indonesian Pesantren - Siti Nihayati Aribah; Intan Pradita (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2022)
This self-observation report aims to investigate the translanguaging practices of teacher-students’ interactions in multilingual classrooms in an International Islamic Boarding School (henceforth: Pesantren). Since Pesantren is a multilingual and multicultural melting pot for Islam-based character building, it is necessary for English teachers in Pesantren to consider some relevant teaching approaches that merit to the needs of multilingual classrooms. Through extensive navigation, we found that translanguaging is one of referred teaching approaches that can accommodate the needs of learning English in multilingual context. However, empirical findings using translanguaging approach in Pesantren is found rare so far. Thus, this study is focused on the use of translanguaging to facilitate English vocabulary learning in a multilingual context. This self-observational report describes the first author’s teaching description about her teaching practices in a Pesantren classroom. She recorded her face-to-face interaction when explaining the meaning and the functions of English vocabularies. She also documented the lesson plans, learning materials, and students’ work to complete the self-observational report. The data were then coded and analyzed with theory-driven thematic analysis. This report found that translanguaging practices that she did were code-switching and code-mixing. When the teacher practiced translanguaging, the students tended to be able to use their L1 (Bahasa Indonesia) and L2 (Arabic) as linguistic resources to learn L3 (English).